2022
DOI: 10.1007/s00520-022-07543-z
|View full text |Cite
|
Sign up to set email alerts
|

“Like one part of a puzzle” — individualized aromatherapy for women with gynecological cancers in aftercare: results from a qualitative-focused mixed-methods study

Abstract: Background Gynecological cancer(s), including breast cancer patients in aftercare and survivors, need supportive strategies to cope with symptoms that are adapted to their individual needs and circumstances. Aromatherapy has potential to be such strategy, but (qualitative) empirical research taking users’ own views into consideration about the potential and challenge of aromatherapy is lacking. Purpose The purpose of the study is to gain insights f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In addition, in the records of Aghamohammadi and collaborators (2018) [ 56 ] and of Arantes et al, 2021 [ 57 ], the intervention contains an extract, not an essential oil. The studies of Czakert [ 58 ] and of Ho [ 59 ] and coworkers are excluded because they perform a qualitative analysis. After title and abstract screening, 22 records are left.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in the records of Aghamohammadi and collaborators (2018) [ 56 ] and of Arantes et al, 2021 [ 57 ], the intervention contains an extract, not an essential oil. The studies of Czakert [ 58 ] and of Ho [ 59 ] and coworkers are excluded because they perform a qualitative analysis. After title and abstract screening, 22 records are left.…”
Section: Resultsmentioning
confidence: 99%
“…These therapies can be diverse and include newer therapies such as aromatherapy or equine therapy in addition to the traditional established methods, which can support the healing process of patients. In a 2022 study, Czakert et al showed that aromatherapy, in particular, can promote the well-being and mindfulness of patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Applying the approach as an integrated approach to the entire research process, not simply for a source of inspiration during data collection, might be promising in terms of a deeper understanding of the content of interest. Further, we cannot exclude that the process, content, and atmosphere of the first part of the interview-concept in the initial study arth4WOMEN (Czakert et al, 2022a) had an influence on the newly developed OLFJ, especially given the nature of interviews as a social action between interviewer and interviewee (Deppermann, 2013). Hence, it remains an open question how the OLFJ may work as a stand-alone data-collection method, which should be taken up in future research.…”
Section: Discussion – About the Trails Contextualization And Continua...mentioning
confidence: 99%
“…This is reflected in the increased research activity and numerous available reviews on AT covering topics such as palliative care needs (Armstrong et al, 2019; Candy et al, 2019), dementia (Ball et al, 2020), or supportive treatment options for people with cancer (Baykal & Comlekci, 2020; Boehm et al, 2012; Chen et al, 2016; Cheng et al, 2022; Li et al, 2022; Toniolo et al, 2021). Subjective perceptions of users regarding essential oil applications, however, seem to be underrepresented in empirical research on AT (Czakert et al, 2022b). The potential benefits and challenges of evoking individual experiences with AT have not yet been considered explicitly in corresponding research to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation